Meeting accreditation standards : a pharmacy preparation guide - Uselton, John P.; Kienle, Patricia C.; Murdaugh, Lee B. (ASHP, 2020)
"This book provides a guide for achieving continuous compliance with accreditation standards relating to pharmacy and medication use. It reflects onsite experiences and survey report results from hundreds of hospitals"--